Lysosomal PIP 3 revealed by genetically encoded lipid biosensors - Ayse Z. Sahan; Mingyuan Chen; Qi Su; Qingrong Li; Dong Wang; Jin Zhang (Proceedings of the National Academy of Sciences, 2025)
3-Phosphoinositides (3-PIs), phosphatidylinositol (3,4) bisphosphate [PI(3,4)P 2 ] and phosphatidylinositol (3,4,5) trisphosphate (PIP 3 ), are important lipid second messengers in the Phosphoinositide 3-Kinase (PI3K)/Akt signaling pathway, which is crucial to cell growth and frequently dysregulated in cancer. Emerging evidence suggests these lipid second messengers may be present in membranes beyond the plasma membrane, yet their spatial regulation within other membrane compartments is not well understood. To dissect the spatial regulation of specific 3-PI species, we developed genetically encodable biosensors with selectivity for PIP 3 or PI(3,4)P 2 . Using these biosensors, we showed that PIP 3 significantly accumulated at the lysosome upon growth factor stimulation, in contrast to the conventional view that PIP 3 is exclusively present in the plasma membrane. Furthermore, we showed that lysosomal PIP 3 originates from the plasma membrane and relies on dynamin-dependent endocytosis for lipid internalization. Thus, PIP 3 can exploit dynamic trafficking pathways to access subcellular compartments and regulate signaling in a spatially selective manner.